Reproductive phenology of two Rhizophora species in Sungai Pulai Forest Reserve, Johor, Malaysia - Nordatul Akmar, Z.; Wan Juliana, W.A. (Penerbit Universiti Kebangsaan Malaysia, 2012)
The reproductive phenology of two mangrove tree species, Rhizophora apiculata and Rhizophora mucronata, were observed monthly for one complete annual cycle from March 2010 until February 2011 at Sungai Pulai Forest Reserve (FR). The objectives of this study were to identify and compare the reproductive phenological patterns of the two species, to determine the duration of flowering and fruiting development, to investigate the percentage of successfulness for each species, and to look at the relationship between rainfall and temperature with reproductive phenological patterns of the two Rhizophora species. Results revealed that both species produced all reproductive units (flower bud, open flower, and fruit) throughout the study period. The flower bud season for R. apiculata was from November until May whilst R. mucronata was from November until April. The flowering season was from June until August for R. apiculata and January until May for R. mucronata. The fruiting season of R. apiculata was from July until January while March until May for R. mucronata. Development from young flower buds to mature propagules took about 14 to 16 months in R. apiculata. Results showed that 7.3% flower buds of R. apiculata gave rise to open flowers and only 1.4% were fertilized. The production of R. mucronata flower buds was significantly (p< 0.05) inversely correlated with the total monthly rainfall and its fruits production was positively correlated with the mean temperature.